A Multifunctional (-)-Meptazinol-Serotonin Hybrid Ameliorates Oxidative Stress-Associated Apoptotic Neuronal Death and Memory Deficits via Activating the Nrf2/Antioxidant Enzyme Pathway. (9th February 2023) - Zhao, Faxue; Zhao, Lin; Zhou, Yan; Tan, Xiaofang; Yang, Yang; Ni, Wenwen; Zheng, Wei; Chen, Hongzhuan; Qiu, Yu; Li, Juan
Abstract : The pathogenesis of Alzheimer's disease (AD) involves multiple pathophysiological processes. Oxidative stress is a major cause of AD-associated neuronal injury. The current research was designed to examine whether a novel (-)-meptazinol-serotonin hybrid (Mep-S) with potent antioxidant activity and additional inhibitory properties for acetylcholinesterase (AChE) activity could attenuate oxidative neuronal damage and cognitive deficits. In human SH-SY5Y cells, Mep-S suppressed H2 O2 -induced apoptosis by restoring mitochondrial membrane potential and inhibiting caspase-3 activation. Meanwhile, it attenuated oxidative stress elicited by H2 O2 through lessening generation of reactive oxygen species as well as enhancing production of glutathione (GSH) and activity of superoxide dismutase (SOD). Mechanistically, Mep-S promoted nuclear translocation of a transcription factor nuclear factor E2-related factor-2 (Nrf2) in H2 O2 -challenged cells. This effect was accompanied by reduction in Kelch-like ECH-associated protein-1 (Keap1) levels as well as augmentation of Akt phosphorylation and expression of heme oxygenase-1 (HO-1) and NAD(P)H quinine oxidoreductase-1 (NQO-1). Molecular docking analysis revealed that Mep-S may disrupt the protein-protein interactions between Keap1 and Nrf2. In an in vivo mouse model, Mep-S attenuated scopolamine-caused cognitive deficits with inhibition of apoptotic neuronal death and brain AChE activity. Furthermore, the scopolamine-induced impairment of total antioxidant capacity and reduction in SOD1, SOD2, and γ -glutamate-cysteine ligase expression in the brain were counteracted by Mep-S, accompanied by decreased Keap1 levels, increased Akt catalytic subunit and Nrf2 phosphorylation, and decreased Nrf2, HO-1, and NQO-1 expression. Collectively, our results suggest that Mep-S ameliorates apoptotic neuronal death and memory dysfunction associated with oxidative stress by regulating the Nrf2/antioxidant enzyme pathway through inactivating Keap1 and phosphorylating Nrf2 via Akt activation. Therefore, Mep-S may be a potential lead for multitarget neuroprotective agents to treat AD-like symptoms.